2024
DOI: 10.1038/s41586-024-07037-4
|View full text |Cite
|
Sign up to set email alerts
|

Light-driven nanoscale vectorial currents

Jacob Pettine,
Prashant Padmanabhan,
Teng Shi
et al.

Abstract: Controlled charge flows are fundamental to many areas of science and technology, serving as carriers of energy and information, as probes of material properties and dynamics1 and as a means of revealing2,3 or even inducing4,5 broken symmetries. Emerging methods for light-based current control5–16 offer particularly promising routes beyond the speed and adaptability limitations of conventional voltage-driven systems. However, optical generation and manipulation of currents at nanometre spatial scales remains a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Therefore, high polarization ratios and responsivities were achieved in mid-infrared photodetection of linearly polarized light and circularly polarized light, even utilizing the topologically trivial photothermoelectric effect. Pettine et al lately revealed the interplay mechanism among electrodynamics, thermodynamics and hydrodynamics which commonly contribute to the plasmonic metamaterials tailored nanoscale vectoral current, and pointed out the wide platform and rich phenomena these nanoscale meta-atoms would create in light-matter interaction …”
Section: Plasmonic Metamaterials Induced Artificial Bpvementioning
confidence: 99%
“…Therefore, high polarization ratios and responsivities were achieved in mid-infrared photodetection of linearly polarized light and circularly polarized light, even utilizing the topologically trivial photothermoelectric effect. Pettine et al lately revealed the interplay mechanism among electrodynamics, thermodynamics and hydrodynamics which commonly contribute to the plasmonic metamaterials tailored nanoscale vectoral current, and pointed out the wide platform and rich phenomena these nanoscale meta-atoms would create in light-matter interaction …”
Section: Plasmonic Metamaterials Induced Artificial Bpvementioning
confidence: 99%